Bimanual examination for clot evacuation: a retrospective cohort study of women with postpartum haemorrhage after vaginal delivery - Pui Ru Koh; Daria Di Filippo; Andrew Bisits; Alec W. Welsh (BMC Pregnancy and Childbirth, 2020)
Abstract Background Bimanual clot evacuation (BCE) is a simple clinical manoeuvre that may reduce need for surgical intervention in the management of severe postpartum haemorrhage (PPH). We sought to determine whether performing BCE in cases of severe PPH after vaginal birth reduces the need for surgical intervention. Methods A retrospective chart review of women who delivered vaginally with a severe PPH between January 1, 2011 and December 31, 2014 in a single tertiary women’s hospital in Sydney, Australia was conducted. Severe PPH was classified as a blood loss ≥1000mls. The need for surgical management (including operating theatre uterine exploration or evacuation, intrauterine balloon tamponade, repair of significant trauma, uterine or internal iliac artery ligation, B-Lynch suture insertion or hysterectomy) was the primary outcome measure, as expressed by need for operating theatre utilisation. Results From a cohort of 438, 149 women (34.0%) had BCE, of whom 29 (19.5%) required surgical management compared to 103 of 289 women with no BCE (35.6%); an odds ratio (OR) of 0.38 for BCE (confidence interval 0.20–0.72; p = 0.003). Early BCE (< 1 h of delivery) was associated with a further reduction in surgery (OR 0.24; confidence interval 0.08–0.70; p = 0.009) compared to late BCE (> 1 h of delivery). There was no reduction in estimated blood loss (p = 0.86) or blood transfusion (p = 0.71) with BCE. Conclusion Our study suggests BCE reduces theatre utilisation in the context of severe PPH following vaginal delivery. Prospective trials are needed to determine whether BCE should be endorsed as a treatment modality for PPH post-vaginal delivery.